Finite Element Analysis (FEA) of Swanson Flexible Hinge Toe Implant (JÓVENES EN LA CIENCIA, 2015)
Hallux Rigidus is an arthritis in the joint of the big toe that make it difficult to walk, run, and bend the toe. The condition can be temporarily relieved by surgery, but silicon elastomer implants can provide extra support in the toe after surgical procedures. The aim of this study was to conduct sensitivity analysis through finite element analysis on the Swanson Flexible Hinge Toe Implant through ANSYS software. ANSYS calculates von-Mises stress, strain, and total deformation on the implant for varying mesh size and applying an angle of 90o in one side of the implant. Through graphical analysis, a mesh size of 2.5 x 10-4 m was selected for optimal results. On the other hand, a structural analysis was performed using this mesh and one side of the implant was fixed and varied forces were applied to the other end to simulate conditions the toe may experience. Also, these forces let us compare the finite element results with the analytical solution for the geometry. Results showed a significant difference between FEM and analytical solution. This highlights the importance of using finite element method for irregular geometries.